The Concept of Organizational Efficiency: an Approach to the University (Revista LIDER, 2020)
The article reviews the concept of efficiency and the challenges ofuniversities. It introduces a distinction between efficiency and effectiveness,and examines ways of measuring. It concludes that there are challenges ahead of standardization and measurement, and research agenda